2017
DOI: 10.1038/bmt.2017.122
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of NK-cell reconstitution after reduced intensity conditioned unrelated cord blood transplantation in patients with acute myeloid leukemia: analysis of a prospective phase II multicenter trial on behalf of the Société Française de Greffe de Moelle Osseuse et Thérapie Cellulaire and Eurocord

Abstract: Unrelated cord blood transplantation (UCBT) after a reduced intensity conditioning regimen (RIC) has extended the use of UCB in elderly patients and those with co-morbidities without an HLA-identical donor, although post-transplant relapse remains a concern in high-risk acute myeloid leukemia (AML) patients. HLA incompatibilities between donor and recipient might enhance the alloreactivity of natural killer (NK) cells after allogeneic hematopoietic stem-cell transplantation (HSCT). We studied the reconstitutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Their activation occurs both by producing interferon-g and by cytotoxic activity, which are especially enriched in UCB grafts. 8,[24][25][26][27] Some studies have reported the potential kinetics of differentiated NK cells with respect to posttransplantation outcomes, especially during relapse, 24,28,29 GVHD, and NRM. 15,24,27,28 In contrast, CD20 1 B cells are well-known as mature B cells that are activated after allogeneic HSCT and show expansion in CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Their activation occurs both by producing interferon-g and by cytotoxic activity, which are especially enriched in UCB grafts. 8,[24][25][26][27] Some studies have reported the potential kinetics of differentiated NK cells with respect to posttransplantation outcomes, especially during relapse, 24,28,29 GVHD, and NRM. 15,24,27,28 In contrast, CD20 1 B cells are well-known as mature B cells that are activated after allogeneic HSCT and show expansion in CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Our study could have benefited from an even larger patient sample size and more frequent lymphocyte subset immunophenotyping assessments. In addition, detailed evaluation of thymopoiesis, including T-cell receptor excision circles 15 and T-cell repertoire diversity, 43,46 virus-specific T-cell responses, 29,39,[48][49][50] and analysis of phenotypic or functional NK-cell reconstitution, 62,70,71 were not routinely performed. These should be investigated in the future to further elucidate the biology of immune recovery after CBT.…”
Section: Discussionmentioning
confidence: 99%
“…The time to NK cell reconstitution (>0.1 × 10 9 /L) was similar between UCBT (1 month) and unrelated BMT (1.4 months), when both groups received ATG as part of the conditioning regimen [30]. Notably, after UCB with no ATG in the conditioning regimen, NK cell count reconstitution at 1 month after UCBT was similar to healthy controls [49,50]. Moreover, a better NK cell reconstitution with higher NK cell counts was observed over a 24-month period in UCBT than PBSCT [31,51].…”
Section: Immune Reconstitution In Ucbtmentioning
confidence: 99%